2022
DOI: 10.1063/5.0114600
|View full text |Cite
|
Sign up to set email alerts
|

Thermal laser evaporation of elemental metal sources in oxygen

Abstract: Thermal laser epitaxy (TLE) is a novel film growth technique capable of fabricating ultrapure films of many material systems. For growing oxide films with TLE, the impact of source oxidation on the evaporation rate is a central issue, which, however, has not yet been explored systematically. Here, we report a systematic, experimental study of the role of source oxidation on source evaporation at various oxygen pressures and source temperatures in TLE. The volatility of the oxidized metal sources affects the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Within TLE, the growth rate can be further increased. In our previous study, we demonstrated a growth rate >3500 Å/s for Al evaporation by a 2000 W laser beam …”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Within TLE, the growth rate can be further increased. In our previous study, we demonstrated a growth rate >3500 Å/s for Al evaporation by a 2000 W laser beam …”
Section: Resultsmentioning
confidence: 91%
“…In our previous study, we demonstrated a growth rate >3500 Å/s for Al evaporation by a 2000 W laser beam. 35 The growth of carbon films, including graphene, on metal substrates is of comparable technical importance to their growth on dielectric substrates. Catalytic metal films, especially those with a hexagonally close-packed (HCP) structure, have been widely employed as substrates for synthesizing single-or multilayer graphene.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…One additional approach to the delivery of refractory elements has emerged over the past 3 years that offers significant promise for the delivery of refractory elements in ultraclean conditions. Using a continuous-wave thermal infrared laser, refractory elements can be evaporated at high deposition rates, comparable to those attained by electron-beam evaporation [74][75][76][77]. With this approach, the surface of a refractory element can be heated to the sublimation or evaporation temperature of the material while the rest of the material remains solid.…”
Section: Thermal Laser Mbementioning
confidence: 99%